Oluf Friisʼ litteraturhistoriske torso – 70 år efter - Conrad, Flemming (Danske Studier, 2024)
This article deals with a history of Danish literature (Den danske Litteraturs Historie) by Oluf Friis. It was published in parts from 1937 and should according to the contract between the author and his publisher be finished within eighteen months. It was obviously meant to be a short and popular presentation. The author, however, lost himself in his work, it swelled beyond all bounds, and in 1945 only one volume, comprising Danish literature up to about 1615, was published. Two more volumes were planned, but none of them saw the light of day. Although it remained a torso, Oluf Friis’ book is an interesting contribution to Danish literary historiography. In particular, his account of the sixteenth century is a scholarly work of value. Here, more than elsewhere, he succeeds in realising his ideal of literary historiography: to describe men of learning as well as poets of a certain period as expressions of the same intellectual current.